Ocorrência de espécies de afídeos em citros (Citrus sinensis (L.) Osbeck), seus predadores e parasitórides - Costa, Fabiano de Mello (Universidade Federal de São Carlos, 2006)
The populational floatation of the aphids Aphis spiraecola (Patch, 1914), Aphis gossypii (Glover, 1887), Toxoptera aurantii (Boyer de Foscolombe, 1841) and Toxoptera citricidus (Kirkald, 1907) was studied and related to climate variations from May of 2004 to April of 2005, through the use of Pearsons s Correlation Analysis. The sampling was carried out every two weeks, through Möericke trap. The highest populational densities of A. gossypii occurred in August and September of 2004, and in the latter the populational peak was verified. From July to September of 2004, it was verified the most intense incidences of T. aurantii, and the highest peak occurred in August of 2004. T citricidus did not present significative correlation with any of the studied climate factors, although higher populational densities in the months of May, June and August of 2004, and the second week of January, 2005, were observed. A. spiraecola predominated over the other species, with populational peaks from May to August of 2004, and in the third week of December of 2004. The populational peak of this specie occurred in August of 2004. It was obtained a positive statistical correlation among the populations of these aphids with thermic extent and the number of dry weather days. Negative correlation, in relation to relative humidity was observed only for A. gossypii. In the space between lines of the citrus culture, 22 infestating plants were identified, among which Annona coriacea M. (Anonaceae), host for T aurantii, Bidens pilosa L. (Asteraceae), host for A. spiraecola, and the infesting Emilia sonchifolia (L) DC (Asteraceae), Sonchus oleraceus L. (Asteraceae), Cassia sp (Leguminosae), Sida glaziovii K. Sch., Sida rhombfolia L., Sida urens L. (Malvaceae), Solanum americanum Mill and Solanum erianthum D. Don (Solanaceae) infested by A. gossypii, must be controlled because they are focuses of aphids that are detrimental to the culture. As for natural enemies, the parasitoid species found more often were the hymenopters of the Aphidiidae Family, Lysiphlebus testaceipes (Cresson, 1880) and Aphidius colemani (Viereck, 1912). In the predatory group, the Coccinellidae Family presented the largest number of species, being Hippodamia convergens (Guérrin-Meneville) the most frequent, followed by Cycloneda sanguinea (Linnaeus, 1763) and then by Scymnus sp, while Olla v-nigrun (Germ., 1824), Hyperaspis (Hyperaspis) festiva (Mulsant, 1850) and Hyperaspis sp. were found in smaller quantity during the sampling period. In the predatory group, the Chrysopidae were more abundante, being identified two species: Chrysoperla externa (Hagen, 1861), Ceraeochrysa cincta (Adams, 1982) and eight examples only identified as Leucochrysa (Nodita) sp. Among the Hemerobiidae, only the specie Nusalala tesselata (Gerstaecker, 1888) was observed in small quantities on the citrus leaves.
Keywords: Hemiptera; Afidoidea; Dinâmica de população; Plantas infestantes; Pragas - controle biológico; CIENCIAS BIOLOGICAS::ECOLOGIA